2022
DOI: 10.1037/bul0000362
|View full text |Cite
|
Sign up to set email alerts
|

Feeling good, doing good, and getting ahead: A meta-analytic investigation of the outcomes of prosocial motivation at work.

Abstract: In recent years, a rapidly growing literature has shed light on important costs and benefits of prosocial motivation in the workplace. However, researchers have studied prosocial motivation using various labels, conceptualizations, and operationalizations, leaving this body of knowledge fragmented. In this study, we contribute to the literature by providing an integrated framework that organizes extant constructs and measures of prosocial motives along two dimensions: level of autonomy (discretionary/obligator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 196 publications
0
18
0
Order By: Relevance
“…‘Doing good feels good’ In recent years, a growing body of evidence attests to the veracity of this simple maxim (Miles et al, 2021 ). Recent studies reported that prosocial behaviors are associated with positive psychological outcomes, including happiness, psychological flourishing, and decreased negative emotions (Curry et al, 2018 ; Hui et al, 2020 ; Liao et al, 2022 ). Moreover, previous findings suggested that prosocial behaviors may be an important component of coping with stress, and engaging in prosocial behavior might be an effective strategy for reducing the impact of stress on emotional functioning (Raposa et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…‘Doing good feels good’ In recent years, a growing body of evidence attests to the veracity of this simple maxim (Miles et al, 2021 ). Recent studies reported that prosocial behaviors are associated with positive psychological outcomes, including happiness, psychological flourishing, and decreased negative emotions (Curry et al, 2018 ; Hui et al, 2020 ; Liao et al, 2022 ). Moreover, previous findings suggested that prosocial behaviors may be an important component of coping with stress, and engaging in prosocial behavior might be an effective strategy for reducing the impact of stress on emotional functioning (Raposa et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by acts of compassion, kindness, and helping, which many people accept as one of the perfect properties of being human. Engaging in prosocial behavior increases the meaningfulness that a person experiences, and prosocialness is positively associated with a person’s well-being (Allan et al, 2018 ; Liao et al, 2022 ). Moreover, engaging in prosocial behavior might be an effective strategy for reducing the adverse effects of emotionally stressful situations (Raposa et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…It can be stated that the voluntary and altruistic idea of additional involvement in a trauma network is beneficial, not least to the supporters of the network. In several studies it could be shown that altruistic behavior and voluntary, honorary engagement leads to the improved well-being of the engaged themselves [ 38 , 39 , 40 , 41 ]. In our concrete example, this leads to the sustainable establishment of a network, in the meantime over more than 10 years, with the largely stable cooperation of the different actors.…”
Section: Establishing the Practitioner Nexusmentioning
confidence: 99%
“…In contrast to the self-interested nature of organizational politics (Ferris et al, 2019), the AL paradigm is an effective leadership approach that promotes positive follower effects (Munyon et al, 2021), representing an important potential boundary condition of the POPS–KS relationship. Similarly, intrinsic and prosocial motivation positively impact work outputs and coworker treatment of others (e.g., Grant, 2008; Liao et al, 2022), suggesting they may also affect the relationship between POPS and KS. Research often evaluates knowledge sharing of individuals (KSI), which may vary from the observed knowledge sharing of the work groups (KSG) in which they function (e.g., Rodriguez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%